Immobilization potential and immobilization mechanism of arsenic in cemented paste backfill. (July 2019) - Li, Yuancheng; Min, Xiaobo; Ke, Yong; Fei, Jiangchi; Liu, Degang; Tang, Chongjian
Graphical abstract: Highlights: Cemented paste backfill exhibited effective immobilization for arsenic waste. AsO 4 3 - substituted SeO 4 2 - inside the ettringite in the form of HAsO 4 2 - . The As-ettringite solid phase was formed as the primary retention phase for As (Ⅴ). Abstract: Although cemented paste backfill (CPB) method has been proposed as a resource disposal technology for arsenic waste, the immobilization potential and immobilization mechanism of arsenic in CPB remain unclear. In this study, lead-zinc slag, gypsum, and sodium arsenate were used to simulate the disposal of arsenic waste in CPB. Toxicity characteristic leaching procedure (TCLP) and compressive strength tests were used to determine the immobilization potential of arsenic in CPB. The immobilization mechanisms of arsenic in CPB were studied by X-ray diffraction (XRD), scanning electronic microscopy-energy dispersive spectrometry (SEM-EDS), and Fourier transform infrared spectroscopy (FTIR). The high compressive strength and low leaching toxicity showed that CPB had better immobilization potential of arsenic. SEM and XRD analyses showed that the formation of As-ettringite is an important immobilization mechanism of arsenic in CPB. FTIR analysis showed that AsO 4 3 - substituted SeO 4 2 - inside the ettringite in the form of HAsO 4 2 - . In the hydration process from 0 to 3 days, physical encapsulation and Ca-As precipitates were the main immobilization mechanism of arsenic. In the hydration process from 3 to 28 days, the immobilization efficiency of As-ettringite on arsenic was significantly higher than that of physical encapsulation and Ca-As precipitation. This study demonstrated that CPB is suitable for the immobilization of arsenic waste.